STUDI RADIOSENSITIVITAS DAN RESPON PERTUMBUHAN STADIA AWAL DUA VARIETAS CABAI RAWIT (Capsicum Frustecens) HASIL IRADIASI SINAR GAMMA - Nabila, Nailan; Setyowati, Ratih; Gumelar, Rima Margareta Retnyo; Huda, Amalia Nurul (MEDIAGRO, 2023)
Cayene pepper is national strategic vegetable commodity which is widely consumed by Indonesian. National pepper consumption has increased in line with increasing population so the production and quality of pepper need to be increased for creating national food security. Increasing the production and quality can be achieved through assembling superior varieties using mutation. The objective of this research are to evaluate the  growth response in early stages of two varieties cayenne pepper irradiated using gamma-ray mutagen and determine the optimal dose of gamma-rays that will increase the frequency of mutant occurrence. This study was conducted in May-July 2023 at the nursery in Wedomartani, Sleman using two factor completely randomized design, namely variety (Ori 212 and Caliber) and doses of gamma irradiation (0, 100, 200, 300, 400, and 500 Gy). Our finding showed that growth of cayenne pepper in the early stages was influenced by the interaction between varieties and doses of gamma-ray irradiation. Gamma rays irradiation by using 100 Gy and 200 Gy at Ori 212 variety and the Caliber variety at dose 100 Gy gave positive response to plant growth at early stage compared to controls. At doses of 400 and 500 Gy gamma rays on the Ori 212 variety, the germinated plants were unable to grow and the plants died. The recommended dose of gamma rays that would increase the frequency of occurrence of mutants were 249.97 – 288.48 Gy for the Ori 212 variety and dose of 383.29 – 521 Gy for the Caliber variety.